Interactions of oleanane pentacyclic triterpenoids with human organic anion transporting polypeptide 1B1 and 1B3 - Tian, Yiqing; Wang, Xue; Bi, Yajuan; Li, Xuejuan; Zhang, Yang; Yao, Yao; Zhang, Mingzhe; Xu, Tong; Zhang, Youheng; Gui, Chunshan; Zhang, Weihua; Zhang, Chunze; et al. (Toxicology in vitro, 2024)
Oleanane pentacyclic triterpenoids have been widely used in clinical practice. However, studies on their interactions with hepatic transporters remain limited. In this study, we systematically investigated the inhibitory effects of 14 oleanane pentacyclic triterpenoids on organic anion transporting polypeptide 1B1 and 1B3 (OATP1B1 and OATP1B3), two liver-specific uptake transporters. Through fluorescence-based cellular uptake assays, we identified three potent OATP1B1 inhibitors (saikosaponin B1, saikosaponin A and 18β-glycyrrhetinic acid) and five potent OATP1B3 inhibitors (echinocystic acid, 3-oxo-16α-hydroxy-olean-12-en-28β-oic acid, chikusetsu saponin IVa, saikosaponin B1 and 18β-glycyrrhetinic acid). Structural analysis revealed that free oleanane triterpenoids inhibited OATP1B1/1B3 more potently than triterpene glycosides. Despite their similar structures, 18β-glycyrrhetinic acid exhibited much stronger inhibition on OATP1B1/1B3 than 18α-glycyrrhetinic acid, while both were substrates of OATP1B3. Interestingly, OATP1B3 overexpression significantly increased reactive oxygen species (ROS) levels in HepG2 cells after treatment with 18β-glycyrrhetinic acid. To conclude, this study highlights the potential interactions of oleanane pentacyclic triterpenoids with OATP1B1/1B3, and provides novel insights into the anti-cancer activity of 18β-glycyrrhetinic acid. •Potent triterpenoid inhibitors of OATP1B1/1B3 were identified.•18α/β-Glycyrrhetinic acids inhibit OATP1B1/1B3 with different potency.•18α/β-Glycyrrhetinic acids were substrates of OATP1B3.•OATP1B3 contributes to the cytotoxicity of 18α/β-Glycyrrhetinic acids.